The Prohibition against Torture: Why the UK Government is Falling Short and the Risks that Remain. Issue 3 (26th April 2019) - Blakeley, Ruth; Raphael, Sam
Abstract: While the UK's official position is that it neither uses nor condones torture or cruel, inhuman and degrading treatment (CIDT), it is now a matter of public and parliamentary record that UK security services and military personnel colluded in rendition, torture, and cruel, inhuman and degrading treatment, both as part of the CIA's Rendition, Detention and Interrogation (RDI) programme, at military detention facilities in Afghanistan and Iraq, and through involvement in the detention and interrogation of prisoners by allied security forces. This paper will explain why the government is falling short of its obligations under international law, and why considerable risks remain that UK intelligence and security services will continue to collude in torture and CIDT.